Cumplimiento y Nivel de Progresividad del Impuesto a la Renta de las Personas Naturales en Ecuador 2001-2005 - Paladines, Eugenio (2007)
This research presents some characteristics of the Ecuadorian personal income tax using micro data from individuals” tax returns during the period from 2001 to 2005. In doing so, high levels of income inequality and important differences in taxpayers” sources of income were identified. Our results suggest that these characteristics considerably affect the personal income tax law compliance as well as its level of progressivity.